What do we know about Objective Structured Clinical Examination in Sport and Exercise Medicine? A scoping review - El Sherif, Reem; Shrier, Ian; Tellier, Pierre-Paul; Rodriguez, Charo (Canadian Medical Education Journal, 2024)
Background and objectives: Despite the importance of the Objective Structured Clinical Examination (OSCE) in Sport and Exercise Medicine, the literature on the topic is fragmented and has been poorly developed. The goal of this review was to map current knowledge about how the OSCE is used in Sport and Exercise Medicine, and to identify knowledge gaps for future research. Method: The authors conducted a scoping review. They searched PubMed and Scopus for articles using key terms related to 'OSCE' and 'sport medicine' with no limit on search start date and up to July 2022. Retrieved records were imported, abstracts were screened, and full-text articles were reviewed. A forward and backward citation tracking was conducted. Data was extracted and a qualitative meta-summary of the studies was conducted. Results: A total of 469 records were screened, and 22 studies were included. The objectives of the studies included using OSCEs to assess knowledge/skills after a training program (n = 11), to assess an intervention (n = 8), and to assess and improve the OSCE itself (n = 3). Thirteen studies reported validity and/or reliability of the OSCE. Conclusion: Despite the widespread use of OSCEs in the examination of Sport and Exercise Medicine trainees, only a handful of scholarly works have been published. More research is needed to support the use of OSCE in Sport and Exercise Medicine for its initial purpose. We highlight avenues for future research such as assessing the need for a deeper exploration of the relationship between candidate characteristics and OSCE scores.